Altered renal expression of aquaporin-2 water channels in rats with experimental two-kidney, one clip hypertension. - Lee, J. (Korean Academy of Medical Sciences, 2001)
The present study was aimed at examining the regulation of aquaporin (AQP)-2 water channels in the kidney in two-kidney, one clip (2K1C) hypertension. Rats were made 2K1C hypertensive for 6 weeks, and their expression of AQP2 channel proteins was determined in the clipped and contralateral kidneys. To examine the upstream affecting AQP2 channels, adenylyl cyclase activity was also determined. Along with the hypertension, in the clipped kidney, the abundance of AQP2 proteins was significantly decreased in the cortex, outer and inner medulla, while their trafficking remained unaltered. Concomitantly with the reversal of the blood pressure at 24 hours following removal of the clip, the AQP2 abundance also returned to the control level. The arginine vasopressin-evoked generation of cAMP was decreased in the clipped kidney, which again was reversed to the control level following removal of the clip. In contrast, the expression of AQP2 channels as well as the activity of adenylyl cyclase remained unaltered in the contralateral kidney. These results indicate an altered regulation of AQP2 water channels in the clipped kidney in 2K1C hypertension.